Processamento das relações correferenciais e sua relação com a memória de trabalho: a influência da distância sintática no processamento anafórico em português brasileiro - Ferreira, Jullyane Glaicy da Costa (2020)
Coreference resolution is a constant linguistic resource in writing and speech, which promotes fluidity, progression, and clarity to the text when used correctly. However, there is still an extensive path of investigation of this phenomenon when it comes to its study from linguistic processing. Studies in the field of Experimental Psycholinguistics have been dedicated to the analysis of differences in procedural costs depending on the type of anaphora resolution (LEITÃO and MELO, 2011; LEITÃO and SIMÕES, 2011; VASCONCELOS and LEITÃO, 2012; and LIMA, 2015). The present work proposes to continue these coreferential studies, focusing on its relationship with working memory, a mental component that, according to Baddeley and Hitch (1974), is responsible not only for storing recent information but also for manipulating it in the realization simultaneous tasks. In a reading process, it is essential that the reader continuously perform mental operations that involve working memory, such as storing, retrieving, and manipulating information. For this reason, it is understood that the processing of the coreference resolution is closely related to working memory. In this relationship between memory and anaphora resolution, the distance factor, between referent and resolution has been relevant in several studies (GORDON et al., 2002; LEITÃO and MELO, 2011; LEITÃO and SIMÕES, 2011; and LIMA, 2015; ARAÚJO, 2019 ) in which the linear distance increased the processing costs in reading sentences, with different results depending on the type of anaphoric correspondence established. It is known that working memory is limited; yet, there is still no consensus among researchers regarding the nature of storable items. Moreover, the syntactic node, here taken as representative of the structure of a phrase, was observed as possible storage and recoverable unit in working memory. Thus, the objective of the study was to verify whether the syntactic distance factor, measured in fits, with 1 and 2 intervening nodes, is configured as a storable unit in working memory, investigating its influence in the processing of different anaphora resolution, known as nome repetido, pronome pleno e categoria vazia. The self-paced reading experimental technique was used in two different experiments. Seventy subjects were tested individually, all university students, who underwent a training session to get used to the task. The results suggest that the syntactic distance is a relevant factor in working memory, with significant procedural differences between conditions with syntactic distance concerning those with linear distance, indicating the formation of chunks. There was an increase in reading times depending on the number of intervening fittings, and different processing costs for each type of anaphora resolution investigated.